Das Wiener Handwerksordnungsbuch (1364-1555) Edition und Kommentar - Gneiß, Markus (2017)
The so-called "Wiener Handwerksordnungsbuch" was compiled by Ulrich Hirssauer, town clerk of Vienna, in the year 1430 and provides a multifaceted picture of everyday life in 15th- and 16th-century Vienna. It not only contains craft ordinances, but also gives information about the organisation of late medieval Viennese marketplaces, the arrangement of civic sentries, the growing and serving of wine and also about both the urban administration and the vicissitude of Viennese history in the 15th century, as numerous official and civic oaths were registered in the manuscript over time. To facilitate the use of the introduction and the edition, the present book comes with a glossary of words, which are not generally intelligible nowadays, and provides indices of persons, places and subjects.